Expression of BTK/p-BTK is different between CD5+ and CD5- B lymphocytes from Autoimmune Hemolytic Anemia/Evans syndromes. Issue 1 (1st January 2019) - Duan, Ningning; Zhao, Manjun; Wang, Yi; Qu, Yingying; Liu, Hong; Wang, Huaquan; Xing, Limin; Shao, Zonghong
ABSTRACT: Objective: To explore the activity of B subsets from Autoimmune Hemolytic Anemia/Evans syndrome (AIHA/ES) patients. Methods: The expression of Bruton's tyrosine kinase (BTK) and phosphorylated BTK (p-BTK) on CD5 + CD19 + B and CD5 - CD19 + B lymphocytes were detected using flow cytometry in AIHA/ES patients with different disease states, healthy controls (HCs) and chronic lymphocytic leukemia (CLL) patients. The correlations of expressed BTK and p-BTK with clinical variables were analyzed. Results: Thirty six AIHA/ES patients (16 hemolytic, 20 remission), 11 CLL patients, and 15 HCs were enrolled. The expression levels of BTK and p-BTK on CD5 + B lymphocytes in AIHA/ES patients were higher than those in HCs and CLL patients. The latter two groups had no significant difference, and were positively correlated with the quantity of IgE. The ratio of p-BTK to BTK on CD5 + B lymphocytes of the hemolytic and remission groups was obviously higher than that on CD5 - B lymphocytes (74.62 ± 6.42% and 29.63 ± 10.19%, respectively; P = 0.001 versus 77.95 ± 9.57% and 26.29 ± 6.86%, respectively; P = 0.006). The ratio of p-BTK to BTK on CD5 + B lymphocytes (54.89 ± 9.56%) and CD5 - B lymphocytes (30.86 ± 12.47%) did not differ significantly in HCs ( P = 0.109). BTK did not differ significantly between CD5 + and CD5 - B lymphocytes in AIHA/ES, but p-BTK on CD5 + B lymphocytes was significantly higher than that on CD5 - B lymphocytes in AIHA/ES patients. Conclusions: CD5 + B lymphocytes are the major B subtype that is activated in AIHA/ES patients and it positively correlates with IgE.